An RFLP-Based Technique for Identifying Fungi in the Sooty Blotch and Flyspeck Complex on Apple - Duttweiler, K B (Plant disease, 2008)
A restriction fragment length polymorphism (RFLP)-based technique was developed to identify members of the sooty blotch and flyspeck (SBFS) disease complex on apple because these fungi are difficult to identify using agar-plate isolation and morphological description. The method includes polymerase chain reaction (PCR) amplification of the internal transcribed spacer (ITS) region of ribosomal DNA (rDNA) using a fungal-specific forward primer (ITS1-F) and an SBFS-specific reverse primer (Myc1-R), followed by digestion of the PCR product by the HaeIII restriction enzyme. When applied to previously identified isolates of 24 SBFS-causing species in nine genera, the PCR-RFLP assay produced 14 unique banding patterns. Different genera never shared the same RFLP pattern. To evaluate performance in vivo, the technique was applied to DNA extracted directly from SBFS colonies on apple fruit from three Iowa orchards. The primers amplified the rDNA of only SBFS fungi, with the exception of a Cladosporium sp.; however, its RFLP banding pattern was distinct from those of SBFS fungi. The majority (60%) of SBFS colonies in the in vivo trial were identified to genus by RFLP analysis. The PCR-RFLP assay greatly streamlined the identification process by minimizing the need for culturing, indicating its value as a tool for field studies of the SBFS complex